Impacting factors and properties of limestone calcined clay cements (LC3). Issue 1 (13th December 2018) - Scrivener, Karen; Avet, François; Maraghechi, Hamed; Zunino, Franco; Ston, Julien; Hanpongpun, Wilasinee; Favier, Aurélie
Abstract : This paper details the main factors influencing the performance of limestone calcined clay cements (LC 3 ). The kaolinite content plays a major role in the rheological properties as well as strength development. Even in the presence of secondary phases, kaolinite can be accurately quantified by thermogravimetric analysis. The performance of LC 3 is slightly influenced by the calcination process of clay, but it can be optimized by using the correct calcination temperature and applying a specific mix design with adjusted sulfate and alkali content. The hydration reactions of LC 3 are fully characterized. They vary slightly from plain cement. There is no significant change in terms of phase assemblage. The main properties of LC 3 are also described. LC 3 blends show a lower creep compliance and a delay in shrinkage strains compared with plain cement. Concerning durability, LC 3 blends show outstanding performance with respect to resisting chloride ingress and expansion from the alkali–silica reaction.